Topical pharmacological treatments for melasma (Research, Society and Development, 2023)
Melanosis is a common acquired hyperpigmentation condition characterized by symmetrical brownish patches on sun-exposed skin. It is a chronic and recurrent disease that mainly affects women. Several factors such as genetic predisposition, sun exposure, pregnancy and hormonal imbalances contribute to its development. Melanosis is classified into three main types, which influence pharmacological treatment and prognosis. The purpose of pharmacological treatment is to lighten the lesions and prevent their expansion, using whitening active ingredients such as kojic acid, mandelic acid, hydroquinone, tranexamic acid, azelaic acid, retinoic acid, glycolic acid and vitamin C. Adequate photoprotection, including daily use of sunscreen, is essential. Despite the existence of available pharmacological treatments, the understanding of the pathophysiological mechanisms of melanosis is still limited. Further studies are needed to develop new treatment strategies. In this context, an integrative review was carried out with the objective of indicating the most used pharmacological treatments of topical administration and more effective for therapy.